Degradation of Alizarin Red by Hybrid Gas-Liquid Dielectric Barrier Discharge - 林启富 倪国华 江贻满 吴文伟 孟月东 (Plasma science & technology, 2014)
A system based on dielectric barrier discharge （DBD） with improved discharge sta- bility and homogeneity was used for the degradation of Alizarin Red （AR）. This special structure of the DBD system is characterized by the high voltage electrode, which is covered with a quartz tube and partially immersed in water, and by directly using the water as the ground electrode. A transition was realized from the filamentary mode for the conventional structure of the DBD to the semi-homogeneous mode for such a configuration of the plasma discharge. The spectra of plasma are dominated by N2 molecular lines in the ultraviolet-A radiation region. Plasma degra- dation of AR in this system exhibited pseudo-first-order reaction kinetics. The degradation rate of AR reached 95% or so after 14 min treatment under favorable conditions. Alkaline conditions are favorable for the degradation of AR. The increase of conductivity of the solution, input power and usage of oxygen bubbling could enhance AR degradation.